Perbedaan Tekanan Mesin Cetak Pneumatik terhadap Kualitas Fisik Permen Ternak: The Pressure Differences in Pneumatic Machine on the Physical Quality of Cattle Candy - Mirza Aulia Rahman; D Suhendra; Y L R E Nugrahini; I Taufik; R W Idayanti; T P Rahayu; N Hidayah (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
Cattle candy is made using a pneumatic machine, namely the pressure force generated by the air pressure coming from the compressor. This study aimed to examine the effects of different pressures in cattle feed supplement pneumatic machines on physical quality, including moisture content, density, durability, and specific gravity. The cattle candy was made from pollard (30%), brown rice bran (10%), molasses (35%), limestone (8%), salt (5%), premix (2%), urea (5%), white cement (2%) and turmeric flour (3%). The candy was made in a size of 1 kg with a diameter of 17 cm. The research design used a completely randomized design (CRD) which consisted of 4 treatments (pressure differences of 5, 6, 7 and 8 bars) with 5 replications. The results showed that the pressure difference of 5-8 bars did not affect the physical quality (moisture content, density, impact resistance, and specific gravity) of cattle candy. The candy had a range of moisture content, density, durability and the specific gravity of 0.88%-0.90%, 0.93-0.94 g cm-3, 99.94%-100.00%, and 1.21-1.29 g mL-1, respectively. The conclusion of this study was that the pressure of 5-8 bars had not changed the physical quality of cattle candy. The use of low pressure (5 bars) was enough to produce good-quality cattle candy. Key words: cattle candy, physical quality, pneumatic, pressure